Zoom Cloud Meeting: Media Alternatif dalam Pembelajaran Maharah Kalam di Tengah Wabah Virus Corona (Covid-19) - Mubarak, Mahfuz Rizqi; Wahdah, Nurul; Ilmiani, Aulia Mustika; Hamidah, Hamidah (Arabiyatuna: Jurnal Bahasa Arab, 2020)
This paper explores the stages of speaking skill's online lectures using the Zoom Cloud Meeting media as well as the advantages and disadvantages of the Zoom Cloud Meeting media. This study used a descriptive qualitative approach with three data collection techniques, namely observation, interviews, and documentation. The results showed that there were several stages used by lecturers in the implementation of speaking skill lectures using Zoom Cloud Meeting media, namely: (1) Pre-Lecture, (2), Lecture Implementation, (3) and Class Evaluation. There are several features of the Zoom Cloud Meeting media used by lecturers in the implementation of speaking skill lectures such as Schedule, mute & unmute, record, chat, and whiteboards. Researchers also found several advantages regarding the implementation of speaking skill lectures using Zoom Cloud Meeting media such as flexibility in the lecture process, increasing discipline for lecturers and students, and several additional features that can support the smooth implementation of lectures. However, the implementation of lectures using this media is also inseparable from shortcomings such as a poor internet network and limited duration of the free Zoom Cloud Meeting media which can only be used for 40 minutes. From the results of this study, it is hoped that it can provide alternative solutions for lecturers in dealing with online lectures in the midst of the COVID-19 pandemic.